2011
DOI: 10.1245/s10434-011-1951-5
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Resection of Primary Tumor in Patients with Stage IV Colorectal Cancer: Retrospective Analysis of Two Randomized Studies and a Review of the Literature

Abstract: BackgroundIn patients with metastatic colorectal cancer (mCRC) with an asymptomatic primary tumor, there is no consensus on the indication for resection of the primary tumor.MethodsA retrospective analysis was performed on the outcome of stage IV colorectal cancer (CRC) patients with or without resection of the primary tumor treated in the phase III CAIRO and CAIRO2 studies. A review of the literature was performed.ResultsIn the CAIRO and CAIRO2 studies, 258 and 289 patients had undergone a primary tumor resec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(97 citation statements)
references
References 50 publications
1
90
0
6
Order By: Relevance
“…A major draw-back of these studies was that patients with better prognosis at the moment of diagnosis were more likely to undergo surgery. An analysis of patients from CAIRO and CAIRO2 studies showed a benefit in overall survival and progression-free survival for patients in which the primary tumour resection was performed [12]. These data can be influenced by the criteria used for selecting patients and depend on the extent of the metastatic disease and the condition of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…A major draw-back of these studies was that patients with better prognosis at the moment of diagnosis were more likely to undergo surgery. An analysis of patients from CAIRO and CAIRO2 studies showed a benefit in overall survival and progression-free survival for patients in which the primary tumour resection was performed [12]. These data can be influenced by the criteria used for selecting patients and depend on the extent of the metastatic disease and the condition of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, the efficacy of initial primary tumour resection is uncertain. Recently, results from amount of studies and retrospective analyses have shown that the resection of the primary tumour provides some benefits to patients with unresectable colorectal metastases in terms of both the OS and PFS [11][12]. On the other hand, Poultsides George et al [13] reported based on a prospective institutional database that most patients with synchronous mCRC who have receive up-front modern combination chemotherapy never require palliative surgery for their intact primary tumour.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that avoiding resection of the primary tumor was acceptable because, in a high proportion of patients, possible complications associated with the primary tumor did not compromise survival [13]. Nonetheless, some analysts suggest a benefit in survival associated with the resection of the primary tumor in patients with mCRC [14][15][16][17][18]. New prospective studies including CLIMAT-PRODIGE 30, CAIRO 4, and SYN-CHRONOUS are currently evaluating this question.…”
Section: Resection Of the Primary Tumor And Its Influence On Survivalmentioning
confidence: 99%
“…Also, age, PS, and comorbidities help to define the treatment strategy for many patients [7,9]. Regarding the question of carrying out surgery in the primary tumor, this procedure is not always required [13][14][15][16][17][18]. In addition, the location of the CRC may have prognostic and predictive implications on response to treatment or on treatment resistance [20,24,25].…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%